PERLINDUNGAN HUKUM TERHADAP ANAK BERKONFLIK DENGAN HUKUM DI LEMBAGA PEMASYARAKATAN - Bella Rizky Armany; Husni H; Ummi Kalsum (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2020)
Law Number 11 of 2012 concerning the Criminal Justice System for Children Article 1 Section (1) number 3 children in conflict with the law are children who are 12 years old but not yet 18 years old who are suspected of committing a criminal act. We can see the legal protection for children. when the child is in conflict with the law and is subject to imprisonment with the loss of rights that the child has. The conditions for handling children who commit criminal acts are very worrying, because some children who are in conflict with the law are brought together in adult prisons.